免疫原性細胞死適用のためのシステムおよび方法 (2025)
本開示は一般的に、例えば加齢、アテローム性動脈硬化症、肥満、ウイルス性疾患などの疾患または状態を治療および予防するためのシステムおよび方法に関する。これらは、いくつかの実施形態によれば、対象内の免疫応答の活性化によって治療し得る。いくつかの実施形態において、例えば、加齢は、免疫系による老化細胞の除去によって治療または予防し得る。いくつかの実施形態において、アテローム性動脈硬化症は、免疫系によるプラークの除去によって治療または予防し得る。いくつかの実施形態において、肥満は、免疫系による脂肪細胞の除去によって治療し得る。いくつかの実施形態において、ウイルス性疾患は、免疫系によるウイルスの除去によって治療し得る。例示的なウイルス性疾患としては、とりわけ、ＳＡＲＳ－ＣｏＶ－２およびＨＩＶによって引き起こされる疾患が挙げられる。 The present disclosure generally relates to systems and methods for treating and preventing diseases or conditions such as aging, atherosclerosis, obesity, viral disease, etc. These may be treated, according to some embodiments, by activation of an immune response within a subject. In some embodiments, for example, aging may be treated or prevented by removal of senescent cells by the immune system. In some embodiments, atherosclerosis may be treated or prevented by removal of plaque by the immune system. In some embodiments, obesity may be treated by removal of fat cells by the immune system. In some embodiments, viral diseases may be treated by removal of viruses by the immune system. Exemplary viral diseases include diseases caused by SARS-COV-2 and HIV, among others.